Quantifying Street Tree Regulating Heat Effects Using a Generalized Linear Mixed Model Approach - Rosos Djikpo, Vignon Adelphe; Teka, Oscar; Abalo, Sandrine; Hozanhekpon, Elodie; Noudehou, Ghislaine; Sinsin, Brice (European Scientific Journal, ESJ, 2023)
Climate change has emerged as a significant global environmental concern, prompting increased interest in utilizing trees as an alternative means to enhance human well-being and thermal comfort in urban settings. This study endeavors to assess the influence of street trees on the urban microclimate in tropical cities, employing a Generalized Linear Mixed Model (GLMM) approach. The investigation was conducted in Cotonou, Porto-Novo, and Ouidah within Benin. Data collection was conducted along thoroughfares, where a systematic inventory was performed to measure various characteristics of each street tree. Meteorological data, encompassing air temperature, relative humidity, and wind speed, were recorded at three different heights thrice an hour from 7 a.m. to 7 p.m. Subsequently, these datasets were analyzed using GLMMs. A total of 1127 street trees belonging to 20 species and 13 families were identified. The Shannon Diversity Index and Pielou Equitability values ranged from 2.33 to 2.92 bits and 0.17 to 0.64, respectively. The GLMM analysis revealed that the presence of trees, daytime, and height significantly influenced air temperature, relative humidity, and wind speed. Street trees on both sides of roadways induced an air temperature decrease from -0.6°C to -1.4°C and an increase in relative humidity ranging from +2.5% to +5.2% between 11 am and 5 pm, as compared to other layouts. Furthermore, closed canopy patterns exhibited the most favorable outcomes, resulting in an air temperature decrease from -0.4°C to -1°C and an increase in relative humidity from +2.4% to +5.5% between 11 am and 5 pm.